Gender and students' views of parental and peer mathematics anxiety :effects on mathematics achievements - Wong, Jing Ling (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aimed to determine the relationships between secondary school students’ mathematics anxiety, their views of parents’ and peers’ mathematics anxiety and mathematics achievement. This research also investigated differences in the variables in terms of gender. A total of 300 Form Four students from two schools in Sibu and four schools in Kuching participated in this orrelational and comparative survey research. This study used a questionnaire adapted from the Mathematics Anxiety Rating Scale-Revised to collect the required data collection. In addition, students’ mathematics marks in their first semester examination represented the measurement of their mathematics achievement. In this study, Pearson-product moment correlations were used to determine the relationships between students’ mathematics anxiety, their views of parents’ and peers’ mathematics anxiety and mathematics achievements. Furthermore, independent t-test analyses were used to determine the differences in students’ mathematics anxiety, their views of parents’ and peers’ mathematics anxiety, and their mathematics achievement between male and female students. This research findings indicated that students’ mathematics achievement was significant and negatively correlated with their views of parents’ mathematics anxiety, their views of peers’ mathematics anxiety and their own mathematics anxiety. On the other hand, the students’ mathematics anxiety was significant and positively correlated with their views of parents’ and peers’ mathematics anxiety. Only students’ views of their peers’ mathematics anxiey were significant different for males and females. Female students viewed that their peers had lower mathematics anxiety compared to male students. There was no significant difference between male and female students in their mathematics achievement, their views of parents’ mathematics anxiety and their own mathematics anxiety.